Effect of dam discharges and tides to transport of Yangtze River using coastal acoustic tomography systems - Xiao, Cong; Zhu, Xiao-Hua; Zhu, Zenan; Zhang, Chuanzheng; Zheng, Hua; Zhang, Zhensheng; Zhong, Jiwen; Wei, Lixin (Frontiers in Marine Science, 2022)
The streamflow characteristics within the Yangtze River Basin have experienced substantial fluctuations in recent years because of the combined effects of environmental factors and intensive human activities. In this study, at the Datong station, two coastal acoustic tomography (CAT) systems were used to track the Yangtze River discharge from July 2018 to January 2021. The stage–discharge relationship presented large uncertainties because of the Three Gorges Dam (TGD) operations, whereas the CAT method performed effectively in discharge monitoring even during extreme flood events. The distribution of downstream discharge was concentrated because of the regulation by the TGD. Analysis of the potential drivers in the downstream river hydrology reveals that the effect of rainfall events (leading to a maximum of 40% changes) was heavily influenced by the regulation by the TGD (at least 50% contribution). Additionally, the river–tide process is also sensitive to the discharge regulated by the TGD. The discharge induced by tidal waves was negligible (a maximum of 1.11% change). This work demonstrates that an acoustic method can effectively monitor the massive flood discharge in unsteady flow conditions in large rivers, thereby facilitating the management of large-scale dam- and tide-influenced river systems.